Protection of Indonesian Migrant Workers in China: The Government's Role and Legal Aspects (Universitas Negeri Semarang, 2022)
This study seeks to examine the model of government accountability for protecting Indonesian migrant workers in China. The expected goal of this research is to make a positive contribution to the legal protection system for Indonesian migrant workers in China that is in harmony with justice and can create a sense of peace and security for Indonesian migrant workers in China. This research was carried out with an empirical juridical approach by analyzing primary data by searching for data by going directly to the field and then analyzing it with legal materials, especially primary legal materials and secondary legal materials. Data observation will be carried out using field studies connected with the subject matter studied. The findings and novelties in this study indicate that migrant workers are often objects of human rights violations, such as not getting guaranteed rights and placements when the migrant workers go abroad through illegal labor suppliers. Especially in this case, the crew from Indonesia works on the Chinese ship, the Longxing Ship. This study concludes that problems related to migrant workers must get full attention and protection from the Government because it concerns the safety of Indonesian citizens. Therefore, in this case, the Tegal Regency Manpower and Transmigration Office, the Government must provide full protection to Indonesian migrant workers. In particular are crew members from Indonesia who work on Chinese ships.